Immune and functional states of lymphocytes in different clinical variants of physical growth and development retardation at children and teenagers as a result of immune-endocrine correlation - T. V. Saprina; Ye. B. Kravets; L. M. Ogorodova (Бюллетень сибирской медицины)
For the study of hormonic-immunologic correlation a clinical model has been chosen that included two variants (somatotrophic deficiency and constitutional growth and pubertate inhibition) of physical growth and development retardation at children and teenagers. It has been revealed that immunologic changes under these dwarfism variants were of different character that reflected the hormonic effects on immunity parameters.